Smart Physicochemical-triggered Chitosan-based Nanogels for siRNA Delivery and Gene Therapy: A Focus on Emerging Strategies and Paradigms for Cancer Therapy - Naghib, Seyed Morteza; Ahmadi, Bahar; Mozafari, Mohammad Reza (Current Medicinal Chemistry, 2025)
Cancer therapy has seen significant advancements in recent years, with the emergence of RNA interference (RNAi) as a promising strategy for targeted gene silencing. However, the successful delivery of small interfering RNA (siRNA) to cancer cells remains a challenge. Chitosan nanoparticles (CSNPs) can be derived from the natural polysaccharide chitin sources. CSNPs have gained considerable attention as a potential solution to encapsulate siRNA due to their biocompatibility, and biodegradability. This article explores the application of CSNPs for siRNA delivery in cancer therapy. Firstly, it discusses the significance of siRNA in gene regulation and highlights its potential to selectively silence oncogenes or tumor suppressor genes, making it a powerful tool in cancer treatment. The obstacles associated with effective siRNA delivery, such as degradation by nucleases and poor cellular uptake, are also addressed. Next, the focus shifts to the unique properties of CSNPs that make them attractive for siRNA delivery. The discussion revolves around how chitosan can interact electrostatically with siRNA to create stable complexes, as well as the controlled release of siRNA from CSNPs. This controlled release ensures sustained and efficient delivery of siRNA to cancer cells, maximizing therapeutic efficacy. Moreover, the biocompatibility and biodegradability of CSNPs make them ideal for in vivo applications. Different approaches to modifying and functionalizing surfaces are investigated by emphasizing on enhancement of stability and targeting abilities of CSNPs in cancer treatment. Registered trials for CS and siRNA are summarized, along with ongoing investigations into various applications of chitosan in medical treatments. Overall, the application of CSNPs in siRNA delivery for cancer therapy holds great promise and offers a potential solution to overcome the challenges associated with RNAi-based treatments. Continued advancements in this field will likely lead to improved targeted therapies with reduced side effects, ultimately benefitting cancer patients worldwide.
Keywords: cancer therapy